ELECTRONIC WORD OF MOUTH AND CONSUMER TRUST ON PURCHASE INTEREST - Sakilah, Arinal Marhamah Nur; Supriyono, Supriyono (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: The spread of Covid-19 requires all activities to be carried out completely online, including shopping activities that utilize the marketplace, one of which is Bukalapak. This study is useful in knowing the influence of E-WOM and consumer confidence in purchase interest in the Bukalapak marketplace. Methods: This study uses a quantitative approach. The study population is visitors of Bukalapak marketplace from Surabaya. The sampling technique used non-probability sampling and the respondent sampling technique through accidental sampling, in order to obtain 77 respondents. Information collection is done by distributing questionnaires to respondents using Google Forms with a Likert scale from a score range of 1 to 5. Then the data is processed using Partial Least Square (PLS) data analysis techniques using validity tests, reliability tests, structural model tests and hypothesis testing. Results The results of the study show that E-WOM and consumer trust have a positive and significant influence on buyer interest in the Bukalapak marketplace. This means that E-WOM and consumer confidence contribute to the purchase interest of visitors in the Bukalapak Marketplace in Surabaya. Conclusion and suggestion: This study is conducted to build interest in buying as measured by electronic word of mouth and consumer trust in Bukalapak, it is hoped that sellers in Bukalapak will pay more attention to every comment and review that comes in and then give a good response so that in the future trust and buying interest from other consumers will increase. Thus, Bukalapak can develop its marketing strategy based on the results of this study, so that it becomes a marketplace that consumers always rely on.